Comparisons of Underlying Mechanisms, Clinical Efficacy and Safety Between Anti-PD-1 and Anti-PD-L1 Immunotherapy: The State-of-the-Art Review and Future Perspectives - Zhao, Yating; Liu, Liu; Weng, Liang (Frontiers in Pharmacology, 2021)
Over the past decade, diverse PD-1/PD-L1 blockades have demonstrated significant clinical benefit in across a wide range of tumor and cancer types. With the increasing number of PD-1/PD-L1 blockades available in the market, differences between the clinical performance of each of them started to be reported. Here, we provide a comprehensive historical and biological perspective regarding the underlying mechanism and clinical performance of PD-1/PD-L1 blockades, with an emphasis on the comparisons of their clinical efficacy and safety. The real-world evidence indicated that PD-1 blockade may be more effective than the PD-L1, though no significant differences were found as regards to their safety profiles. Future head-to-head studies are warranted for direct comparison between them. Finally, we summarize the yet to be elucidated questions and future promise of anti-PD-1/PD-L1 immunotherapy, including a need to explore novel biomarkers, novel combinatorial strategies, and their clinical use on chronic infection.